Bibliometric Trends in Cultural Heritage and Film Studies: Reviving Ancestral Legacy in The Digital Age - Hasni Hasni; Hasnawi Haris; M. Yunasri Ridhoh (Universitas Lambung Mangkurat, 2025)
Cultural heritage with traditional based modern technology can be used to revive and spread ancient traditions. This study aims to analyze and find out the use of film in social studies in the world. The research method is literature review analysis with data sources from various scientific journals in the scopus database. Data analysis using the keywords TITLE-ABS-KEY (